Names as resources for gendering - Emilia Aldrin (Nordisk Tidskrift för Socioonomastik, 2025)
This article discusses personal names as a crucial linguistic resource for the construction of gender-related identities. It identifies and discusses trends in research on naming and gender, aiming to highlight key publications, point out changes over time, and suggest fruitful areas for further research. Using a personal name constitutes a categorizing linguistic act that contributes to the construction of gender identities, as well as indexically linking assumptions about gender-related embodiments, roles, and identities to specific types of denominations. Moreover, name usage creates conditions for renegotiating or breaking existing gender-related norms. Research on naming and gender is a well-established international and interdisciplinary field of study. This article particularly emphasizes Nordic studies but does so based on references to a broad international research context.